Exploring green extraction methods to obtain polyphenols from partially defatted chia (Salvia hispanica L.) flour - Antón, Micaela (2023)
The extraction of polyphenols is commonly accomplished using conventional techniques such assolid-liquid and liquid-liquid extraction, which are associated with the use of high quantities of organicsolvents, long extraction times, and low selectivity and reproducibility. These limitations have led to thedevelopment of innovative extraction technologies. The purpose of this study was to investigate theultrasound-assisted extraction (UAE) and microwave-assisted extraction (MAE) of polyphenols frompartially defatted chia flour (PDCF).